Care and Covenant: A Jewish Bioethic of Responsibility - Weiner, Jason (Georgetown University Press, 2023)
A bioethic of obligations and responsibilities, based on the Jewish tradition The Jewish tradition has important perspectives, history, and wisdom that can contribute significantly to crucial contemporary healthcare deliberations. Care and Covenant: A Jewish Bioethic of Responsibility demonstrates how numerous classic Jewish texts can add new ideas to the world of medicine today. Rabbi Jason Weiner draws on fifteen years of experience working in a hospital as a practitioner to develop an "ethic of responsibility." This book seeks to develop an approach to bioethical dilemmas that is primarily informed by personal and communal obligations as well as social responsibilities. Weiner applies unique and inspiring values found in Judaism to encourage healthcare providers to remain dedicated to preventing harm and providing care to all. Each chapter investigates relevant philosophical questions such as what the expectations of a society or government are and what we should do when our obligations to others violate our own moral principles, safety, or ability to assist. Care and Covenant provides analytical, philosophical, and evidence-based scholarship to guide discussions on ethics in healthcare.